Role of interleukin-16 in human diseases: a novel potential therapeutic target - Timothy B. Niewold; Julia S. Lehman; Iva Gunnarsson; Iva Gunnarsson; Alexander Meves; Vilija Oke; Vilija Oke (Frontiers in Immunology)
Interleukin (IL)-16 is expressed mostly by the cells of the human immune system. Upon cell activation IL-16 is cleaved, forming two functional proteins, one regulating cell cycle and the other acting as chemoattractant for the cells carrying CD4 or CD9. Increased levels of IL-16 are found in the circulation and at the sites of inflammation, infection and cancer. Polymorphisms in the IL-16 gene have been coupled to several of these conditions and high IL-16 has been suggested as a disease biomarker. Using unbiased proteomic approach we and others independently identified IL-16 as a biomarker of severe lupus nephritis, and top-expressed cytokine in skin lesions of lupus erythematosus. Recently, an unbiased investigation identified IL-16 as a top candidate for novel drug target. Blockade of IL-16 showed positive therapeutic effects in several animal models of human disease with low rate of side effects. Importantly, it has been recently demonstrated that IL-16 can be released during pyroptosis, a proinflammatory cell death pathway. This finding disclosed a novel role of IL-16 as a mediator of response to the proinflammatory cell death and may explain why IL-16 is detected at the sites of inflammation, infection or cancer. In this review we cover the knowledge on the biology of IL-16 and its importance in human diseases. We aim that this manuscript will be informative and prove benefits of possible therapeutic blockade of IL-16.